Direct gasification of biomass for fuel gas production - Pio, Daniel Torrão (2022)
The excessive consumption of fossil fuels to satisfy the world necessities of energy and commodities led to the emission of large amounts of greenhouse gases in the last decades, contributing significantly to the greatest environmental threat of the 21st century: Climate Change. The answer to this man-made disaster is not simple and can only be made if distinct stakeholders and governments are brought to cooperate and work together. This is mandatory if we want to change our economy to one more sustainable and based in renewable materials, and whose energy is provided by the eternal nature energies (e.g., wind, solar). In this regard, biomass can have a main role as an adjustable and renewable feedstock that allows the replacement of fossil fuels in various applications, and the conversion by gasification allows the necessary flexibility for that purpose. In fact, fossil fuels are just biomass that underwent extreme pressures and heat for millions of years. Furthermore, biomass is a resource that, if not used or managed, increases wildfire risks. Consequently, we also have the obligation of valorizing and using this resource. In this work, it was obtained new scientific knowledge to support the development of direct (air) gasification of biomass in bubbling fluidized bed reactors to obtain a fuel gas with suitable properties to replace natural gas in industrial gas burners. This is the first step for the integration and development of gasification-based biorefineries, which will produce a diverse number of value-added products from biomass and compete with current petrochemical refineries in the future. In this regard, solutions for the improvement of the raw producer gas quality and process efficiency parameters were defined and analyzed. First, addition of superheated steam as primary measure allowed the increase of H2 concentration and H2/CO molar ratio in the producer gas without compromising the stability of the process. However, the measure mainly showed potential for the direct (air) gasification of high-density biomass (e.g., pellets), due to the necessity of having char accumulation in the reactor bottom bed for char-steam reforming reactions. Secondly, addition of refused derived fuel to the biomass feedstock led to enhanced gasification products, revealing itself as a highly promising strategy in terms of economic viability and environmental benefits of future gasification-based biorefineries, due to the high availability and low costs of wastes. Nevertheless, integrated techno economic and life cycle analyses must be performed to fully characterize the process. Thirdly, application of low-cost catalyst as primary measure revealed potential by allowing the improvement of the producer gas quality (e.g., H2 and CO concentration, lower heating value) and process efficiency parameters with distinct solid materials; particularly, the application of concrete, synthetic fayalite and wood pellets chars, showed promising results. Finally, the economic viability of the integration of direct (air) biomass gasification processes in the pulp and paper industry was also shown, despite still lacking interest to potential investors. In this context, the role of government policies and appropriate economic instruments are of major relevance to increase the implementation of these projects.